Effect of infill wall and wall openings on the fundamental period of RC buildings - Kocak, A.; Kalyoncuoglu, A.; Zengin, B. (WIT PRESS, 2013)
The effect of infill walls to stiffness of the structures has been known for a long time and this effect has taken many of the earthquake regulations with empirical relationships and equations into account. However, in strength-based calculations, buildings are taken as bare frames and infill walls are effected as vertical load to system, whereas infill walls contribute to stiffness at the beginning of the earthquake and help meet seismic loads by incurring damage during an earthquake. In this study, contribution of infill walls to stiffness of the structure was analyzed in reinforced concrete framed and load-bearing buildings. Also, the effect of openings in the infill walls to stiffness was examined.
Keywords: reinforced concrete frame; infill wall; wall openings; period; MASONRY; FRAMES; Engineering; Geology